Personal exposures to air pollutants and respiratory health among brick kiln workers and household members - Laura Nicolaou; Evelyn Rowell; Chelsea Gaviola; Ram K. Chandyo; Arun K. Sharma; Laxman P. Shrestha; Santa Das; David L. Parker; Steven M. Thygerson; Joseph Jacob; Bojidar Rangelov; Ryoko Egashira; et al. (Environmental Research, 2025)

Brick kiln pollution and its impact on health: A systematic review and meta-analysis - Laura Nicolaou; Fiona Sylvies; Isabel Veloso; Katherine Lord; Ram K. Chandyo; Arun K. Sharma; Laxman P. Shrestha; David L. Parker; Steven M. Thygerson; Peter F. DeCarlo; Gurumurthy Ramachandran; William Checkley (Environmental Research, 2024)

Improving landings forecasts using environmental covariates: A case study on the Indian oil sardine ( Sardinella longiceps ) - Elizabeth Eli Holmes; Smitha BR; Kumar Nimit; Sourav Maity; David M. Checkley; Mark L. Wells; Vera L. Trainer (Fisheries Oceanography, 2021)
Commercial landings of sardines are known to show strong year‐to‐year fluctuations. A key driver is thought to be environmental variability, to which small forage fish are especially sensitive. We examined the utility of including environmental covariates in forecasts for landings of the Indian oil sardine using a long‐term time series of quarterly catches. Potentially influential variables examined included precipitation, upwelling intensity, sea surface temperature (SST), and chlorophyll‐a concentration. All of these have been shown to be important for oil sardine growth and survival, spawning and/or movement into the nearshore fishing regions. However, improving out‐of‐sample landings forecasts using environmental covariates has often proven elusive. We tested the inclusion of environmental covariates in forecast models using generalized additive models, which allow for non‐linear responses, and dynamic linear models, which allow for time‐varying responses. Only two environmental covariates improved out‐of‐sample prediction: the 2.5‐year average regional SST and precipitation over land during June–July. The most significant improvement was with the SST covariate and post‐monsoon landings with a 19%–22% reduction in mean‐squared prediction error. Models with the second best covariate, monsoon precipitation over land, provided a 4%–8% reduction in prediction error. We also tested large‐scale ocean climate teleconnection indices. One, an index of the Atlantic Multidecadal Oscillation, also improved out‐of‐sample predictions similarly to the multiyear average regional SST. The earth's changing climate is associated with both rapid warming in the Western Indian Ocean and changes to monsoon rainfall patterns. Our work highlights these as key variables that can improve forecasting of oil sardine landings.

Climate variability and sardine recruitment in the California Current: A mechanistic analysis of an ecosystem model - Dimitrios V. Politikos; Enrique N. Curchitser; Kenneth A. Rose; David M. Checkley; Jerome Fiechter (Fisheries Oceanography, 2018)
Recruitment varies substantially in small pelagic fish populations. Understanding of the mechanisms linking environment to recruitment is essential for the effective management of fisheries resources. In this study, we used a fully coupled end‐to‐end ecosystem model to study the effect of climate variability on sardine recruitment in the California Current System during 1965–2006. Ocean variability was represented by ROMS hydrodynamic and NEMURO biogeochemical models, and sardine population dynamics was simulated through a full life cycle individual‐based model. Model analysis was designed to elucidate how changes in abiotic and biotic conditions may impact the spawning habitats, early life stage survival, and ultimately recruitment of sardine. Our findings revealed the importance of spatial processes to shape early life stages dynamics. Shifts in spawning habitats were dictated by the spatial variations in temperature and the behavioral movement of adults. Additionally, the spatial match of eggs with warmer temperatures and larvae with their prey influenced their survival. The northward shifts in spawning locations and the accomplishment of good recruitment in warmer years agreed with existing knowledge. Egg production and survival during egg and yolk‐sac larval stages were key factors to drive the long‐term variations in recruitment. Finally, our analysis provided a quantitative assessment of climate impact on year‐to‐year variation in sardine recruitment by integrating multiple hypotheses.

Linking Capacity Development to GOOS Monitoring Networks to Achieve Sustained Ocean Observation - Nicholas J. Bax; Ward Appeltans; Russell Brainard; J. Emmett Duffy; Piers Dunstan; Quentin Hanich; Harriet Harden Davies; Jeremy Hills; Patricia Miloslavich; Frank Edgar Muller-Karger; Samantha Simmons; O. Aburto-Oropeza; et al. (Frontiers in Marine Science, 2018)

Essential ocean variables for global sustained observations of biodiversity and ecosystem changes - Patricia Miloslavich; Nicholas J. Bax; Samantha E. Simmons; Eduardo Klein; Ward Appeltans; Octavio Aburto‐Oropeza; Melissa Andersen Garcia; Sonia D. Batten; Lisandro Benedetti‐Cecchi; David M. Checkley; Sanae Chiba; J. Emmett Duffy; et al. (Global Change Biology, 2018)
Sustained observations of marine biodiversity and ecosystems focused on specific conservation and management problems are needed around the world to effectively mitigate or manage changes resulting from anthropogenic pressures. These observations, while complex and expensive, are required by the international scientific, governance and policy communities to provide baselines against which the effects of human pressures and climate change may be measured and reported, and resources allocated to implement solutions. To identify biological and ecological essential ocean variables ( EOV s) for implementation within a global ocean observing system that is relevant for science, informs society, and technologically feasible, we used a driver‐pressure‐state‐impact‐response ( DPSIR ) model. We (1) examined relevant international agreements to identify societal drivers and pressures on marine resources and ecosystems, (2) evaluated the temporal and spatial scales of variables measured by 100+ observing programs, and (3) analysed the impact and scalability of these variables and how they contribute to address societal and scientific issues. EOV s were related to the status of ecosystem components (phytoplankton and zooplankton biomass and diversity, and abundance and distribution of fish, marine turtles, birds and mammals), and to the extent and health of ecosystems (cover and composition of hard coral, seagrass, mangrove and macroalgal canopy). Benthic invertebrate abundance and distribution and microbe diversity and biomass were identified as emerging EOV s to be developed based on emerging requirements and new technologies. The temporal scale at which any shifts in biological systems will be detected will vary across the EOV s, the properties being monitored and the length of the existing time‐series. Global implementation to deliver useful products will require collaboration of the scientific and policy sectors and a significant commitment to improve human and infrastructure capacity across the globe, including the development of new, more automated observing technologies, and encouraging the application of international standards and best practices.

Climate‐mediated changes in marine ecosystem regulation during El Niño - Martin Lindegren; David M. Checkley; Julian A. Koslow; Ralf Goericke; Mark D. Ohman (Global Change Biology, 2018)
The degree to which ecosystems are regulated through bottom‐up, top‐down, or direct physical processes represents a long‐standing issue in ecology, with important consequences for resource management and conservation. In marine ecosystems, the role of bottom‐up and top‐down forcing has been shown to vary over spatio‐temporal scales, often linked to highly variable and heterogeneously distributed environmental conditions. Ecosystem dynamics in the Northeast Pacific have been suggested to be predominately bottom‐up regulated. However, it remains unknown to what extent top‐down regulation occurs, or whether the relative importance of bottom‐up and top‐down forcing may shift in response to climate change. In this study, we investigate the effects and relative importance of bottom‐up, top‐down, and physical forcing during changing climate conditions on ecosystem regulation in the Southern California Current System ( SCCS ) using a generalized food web model. This statistical approach is based on nonlinear threshold models and a long‐term data set (~60 years) covering multiple trophic levels from phytoplankton to predatory fish. We found bottom‐up control to be the primary mode of ecosystem regulation. However, our results also demonstrate an alternative mode of regulation represented by interacting bottom‐up and top‐down forcing, analogous to wasp‐waist dynamics, but occurring across multiple trophic levels and only during periods of reduced bottom‐up forcing (i.e., weak upwelling, low nutrient concentrations, and primary production). The shifts in ecosystem regulation are caused by changes in ocean‐atmosphere forcing and triggered by highly variable climate conditions associated with El Niño. Furthermore, we show that biota respond differently to major El Niño events during positive or negative phases of the Pacific Decadal Oscillation ( PDO ), as well as highlight potential concerns for marine and fisheries management by demonstrating increased sensitivity of pelagic fish to exploitation during El Niño.

Responses in growth rate of larval northern anchovy ( Engraulis mordax ) to anomalous upwelling in the northern California Current - MOTOMITSU TAKAHASHI; DAVID M. CHECKLEY; MARISA N.C. LITZ; RICHARD D. BRODEUR; WILLIAM T. PETERSON (Fisheries Oceanography, 2012)
We examined variability in growth rate during the larval stage of northern anchovy ( Engraulis mordax ) in response to physical and biological environmental factors in 2005 and 2006. The onset of spring upwelling was anomalously delayed by 2–3 months until mid‐July in 2005; in contrast, spring upwelling in 2006 began as a normal year in the northern California Current. Larval and early juvenile E. mordax were collected in August, September, and October off the coast of Oregon and Washington. Hatch dates ranged from May to September, with peaks in June and August in 2005 and a peak in July in 2006, based on the number of otolith daily increments. Back‐calculated body length‐at‐age in the June 2005 hatch cohort was significantly smaller than in the August 2005 cohort, which had comparable growth to the July 2006 cohort. Standardized otolith daily increment widths as a proxy for seasonal variability in somatic growth rates in 2005 were negative until late July and then changed to positive with intensification of upwelling. The standardized increment width was a positive function of biomass of chlorophyll a concentration, and neritic cold‐water and oceanic subarctic copepod species sampled biweekly off Newport, Oregon. Our results suggest that delayed upwelling in 2005 resulted in low food availability and, consequently, reduced E. mordax larval growth rate in early summer, but once upwelling began in July, high food availability enhanced larval growth rate to that typical of a normal upwelling year (e.g., 2006) in the northern California Current.

Remotely sensed spawning habitat of Pacific sardine ( Sardinops sagax ) and Northern anchovy ( Engraulis mordax ) within the California Current - CHRISTIAN S. REISS; DAVID M. CHECKLEY; STEVEN J. BOGRAD (Fisheries Oceanography, 2008)
We use trivariate kernel density estimation to define spawning habitat of northern anchovy ( Engraulis mordax ) and Pacific sardine ( Sardinops sagax ) in the California Current using satellite data and in situ egg samples from the Continuous Underway Fish Egg Sampler (CUFES) deployed during surveys in April by the California Cooperative Oceanic Fisheries Investigations (CalCOFI). Observed egg distributions were compared with monthly composite satellite sea surface temperature (SST) and surface chlorophyll a (chl a ) data. Based on the preferred spawning habitat, as defined in SST and chl a space, the satellite data were used to predict potential spawning habitat along two areas of the west coast of North America. Data from the southern area (21.5 to 39°N) were compared to observations from the CUFES data for the period 1998–2005. Northern anchovy and Pacific sardine exhibited distinctly different spawning habitat distributions. A significant relationship was found between satellite‐based spawning area and that measured during surveys for sardine. CUFES area estimated for sardine was similar in magnitude to that estimated from satellite data (∼60 000 km 2 ). In contrast, spawning habitat of anchovy averaged between 1000 and 200 000 km 2 for the period 1998–2005, for CUFES and satellite estimates, respectively. Interannual variability in the area (km 2 ) and duration (months) of estimates of suitable habitat varied between species and between the northern (39 to 50.5°N) and southern portions of the California Current. Long‐term monitoring of habitat variability using remote sensing data is possible in the southern portion of the California Current, and could be improved upon in the northern area with the addition of surveys better timed to describe relationships between observed and estimated spawning habitats.

Predicting the vertical profiles of anchovy ( Engraulis mordax ) and sardine ( Sardinops sagax ) eggs in the California Current System - K. ALEXANDRA CURTIS; DAVID M. CHECKLEY; PIERRE PEPIN (Fisheries Oceanography, 2007)
Several published models exist for simulating vertical profiles of pelagic fish eggs, but no one has rigorously assessed their capacity to explain observed variability. In this study, we applied a steady‐state model, with four different formulations for vertical diffusivity, to northern anchovy ( Engraulis mordax ) and Pacific sardine ( Sardinops sagax ) eggs in the California Current region. Vertical mixing profiles, based on wind speed and hydrography, were combined with estimated terminal ascent velocities of the eggs based on measurements of egg buoyancy and size, to simulate the vertical profiles of the eggs. We evaluated model performance with two data sets: (1) vertically stratified tows for both species and (2) paired samples for sardine eggs from 3‐m depth and in vertically integrated tows. We used two criteria: whether the model predicted individual observed vertical profiles (1) as well as the observed mean and (2) better than the observed mean. Model predictions made with the formulation producing the most gradual profile of vertical diffusivity provided the best match to observations from both data sets and for both species. Addition of a random error term to the terminal ascent velocity further improved prediction for anchovy eggs, but not sardine. For the paired data, model prediction of integrated abundance from abundance at 3‐m depth had significantly lower mean square error than prediction based on a linear regression of 3 m on integrated abundance. Our results support the feasibility of using data from the Continuous Underway Fish Egg Sampler quantitatively as well as qualitatively in stock assessments.

A new method to measure the terminal velocity of small particles: A demonstration using ascending eggs of the Atlantic menhaden (Brevoortia tyrannus) - John J. Cambalik; David M. Checkley; Daniel Kamykowski (Limnology and Oceanography, 1998)
A new method, incorporating video, motion analysis, and a novel experimental apparatus, was used to measure the terminal velocity of particles. The method facilitated the investigation of treatment effects and maximized the number of measurements For each replicate, thus improving the statistics for a population of particles. The eggs of the Atlantic menhaden ( Brevoortia tyrannus ) were used to demonstrate the method by investigating the effects of salinity and stage of development on their ascent rate. Egg ascent rate was greatest at intermediate salinity (36.5‰) and decreased in the late stage of embryonic development. We estimate eggs at oceanic salinities (>35.5‰) in nature to ascend at 0.19–0.25 cm s −1 .

Observations of a deep aggregation of Calanus pacificus in the Santa Barbara Basin - Kenric E. Osgood; David M. Checkley (Limnology and Oceanography, 1997)
An optical plankton counter/CTD package was used with zooplankton net samples to map the distribution of fifth copepodid (C5) Calanus pacificus in the Santa Barbara Basin region during two autumn cruises. Diapausing C5 C. pacificus were aggregated in a layer just above the basin’s oxygen‐deficient bottom waters and below its sill depth. The maximal concentration measured was 6,900 ind. m from a net sample spanning a depth range double the thickness of the C5 layer. Although the C5 concentration varied, the layer was found at all stations of sufficient bottom depth within the basin. During November 1994, C5 C. pacificus accounted for 95–97% of all zooplankton caught in net samples from the layer. Relatively low concentrations of deep‐dwelling C5 C. pacificus were observed at nearby stations outside the basin. We hypothesize that C5 C. pacificus descend into the Santa Barbara Basin at diapause, are trapped, and accumulate in a region of relatively low predator abundance. The resultant aggregation is estimated to contain a significant fraction of the regional C. pacificus population and thus assumes an important role in its dynamics.

A continuous, underway fish egg sampler - DAVID M. CHECKLEY JR; PETER B. ORTNER; LAWRENCE R. SETTLE; SHAILER R. CUMMINGS (Fisheries Oceanography, 1997)
We describe a method to sample the highly contagious distribution of pelagic fish eggs. CUFES, the continuous, underway fish egg sampler, consists of a submersible pump, concentrator, electronics and sample collector. This system operates continuously and under nearly all sea conditions, providing a real‐time estimate of the volumetric abundance of pelagic fish eggs at pump depth, usually 3 m. CUFES‐derived estimates of volumetric abundance agree well with those from nets towed at pump depth and with areal abundance estimated from vertically integrated plankton tows. CUFES has been used successfully to sample the eggs of menhaden, pinfish, sardine, and anchovy off the coasts of the eastern and western United States and South Africa. Two large patches of eggs of the Atlantic menhaden were sampled off North Carolina in winter 1993–94, had a linear scale of 5–10 km, and were found in waters between the Gulf Stream and mid‐shelf front. Spawning location may be related to bathymetry. CUFES is now being used to estimate spawner biomass by the daily egg production method. An optical plankton counter provided accurate estimates of the number of Atlantic menhaden eggs sample by CUFES.